Unidad didáctica para mejorar la comprensión lectora en niños de grado tercero a través de cuentos infantiles (2016)
One of the greatest challenges for teachers is to achieve significant progress in their students' reading process. It is well known that language skills - reading, listening, speaking and writing - cannot be one without the other. Hence, by improving reading comprehension, other language skills can be enhanced.